Review on Antimicrobial Polyherbal Cream - Sonwalkar, Viraj S.; Naikwadi, Nishiganda D.; Redasani , V.K.Redasani; Redasani , V.K. (Asian Journal of Pharmaceutical Research and Development, 2024)
This review article explores the effectiveness of antimicrobial creams in addressing microbial infections and supporting skin health. It examines the mechanisms underlying microbial growth on the skin and the diverse range of antimicrobial agents utilized in cream formulations. Special emphasis is placed on the antimicrobial properties of various plants. Through comprehensive analysis, the article underscores the potential of antimicrobial creams as natural alternatives for managing skin infections and enhancing dermatological well-being.